Paleo-shoreline changes in moraine dammed lake Khagiin Khar, Khentey Mountains, Central Mongolia - Oh, Jeong-Sik; Seong, Yeong Bae; Hong, Seongchan; Yu, Byung Yong (SCIENCE PRESS, 2019)
The formation and evolution of glacier moraine-dammed lakes are closely related to past glacier expansion and retreat. Geomorphic markers such as lacustrine terraces and beach ridges observed in these lakes provide important evidence for regional paleoenvironment reconstruction. We document the magnitude of paleo-shoreline fluctuations and timings of highstands of lake water by using cosmogenic Be-10 surface exposure dating and optically stimulated luminescence (OSL) dating on samples collected from lacustrine sediment and bedrock strath in Lake Khagiin Khar. The lake was initially impounded by glacier moraine at the Global Last Glacial maximum (gLGM; 21-19 ka), and the lake reached its maximum paleo-shoreline level of 1840 m at sea level (a.s.l.). At that time, the stored lake water amount was up to seven times greater and the surface area was three times larger than the present values. The paleolake experienced higher shoreline levels at 1832, 1822, and 1817 m a.s.l. and reached the present lake level after 0.4 ka. We interpret that decrease in the paleolake level was caused by spillover. The increase in melt water after the gLGM and the Late Glacial exceeded the storage threshold of the lake, and the paleolake water overflowed across the lowest drainage divides. The lake spilled over across the lowest bedrock ridge at 15.9 +/- 0.6 ka, and the outlet was incised since that time at a rate of 3.72 +/- 0.15 mm/yr. The initial stream of the Khiidiin Pass River was disturbed by LGM moraine damming and was rerouted into the present course running through moraine after the spillover at 15.9 +/- 0.6 ka.
Keywords: COSMOGENIC RADIONUCLIDES; LATE PLEISTOCENE; GLACIAL LAKES; BASIN; QUARTZ; LUMINESCENCE; BE-10; RATES; DRAINAGE; SURFACE